PHILOSOPHICAL ASPECTS PRESENT IN QUESTIONS REGARDING MATHEMATICS TECHNOLOGY AND EDUCATION - Maria Aparecida Viggiani BICUDO; Maurício ROSA (Studia Universitatis Babeș-Bolyai. Philosophia)
This article discusses how intentionality shows itself in cyberspace reality, where the phenomenon perceived stands out in the modern, contemporary life-world. We analyse the manifestation of human intentionality with the cybernetic life-world, based on a film (Dèjá vu, 2006), and underline the idea that this life-world we address sustains teaching and learning actions, among which to educate mathematically, to educate at distance and perceive the other as an equal, when being with the other who presents him/herself in the computer, through currently accessible gadgets. Moreover, we understand that this discussion opens new educational possibilities, to which we have to devote our attention.